RNA-binding strategies common to cold-shock domain- and RNA recognition motif-containing proteins - Manival, Xavier (Oxford University Press, 2001)
Numerous RNA-binding proteins have modular structures, comprising one or several copies of a selective RNA-binding domain generally coupled to an auxiliary domain that binds RNA non-specifically. We have built and compared homology-based models of the cold-shock domain (CSD) of the Xenopus protein, FRGY2, and of the third RNA recognition motif (RRM) of the ubiquitous nucleolar protein, nucleolin. Our model of the CSD(FRG)–RNA complex constitutes the first prediction of the three-dimensional structure of a CSD–RNA complex and is consistent with the hypothesis of a convergent evolution of CSD and RRM towards a related single-stranded RNA-binding surface. Circular dichroism spectroscopy studies have revealed that these RNA-binding domains are capable of orchestrating similar types of RNA conformational change. Our results further show that the respective auxiliary domains, despite their lack of sequence homology, are functionally equivalent and indispensable for modulating the properties of the specific RNA-binding domains. A comparative analysis of FRGY2 and nucleolin C-terminal domains has revealed common structural features representing the signature of a particular type of auxiliary domain, which has co-evolved with the CSD and the RRM.